2007
DOI: 10.1111/j.1467-7660.2007.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Feminism, Gender, and Women's Peace Activism

Abstract: United Nations Security Council Resolution 1325 on ‘Women, peace and security’, passed in 2000, reflects a recent growth in women's peace activism. Women's resistance to violence is widely believed to be a mobilizing factor in both local and international peace movements. This provokes questions around essentialism and violence of concern to feminists: are men inherently territorial and aggressive, and women naturally nurturing and peaceable? Or is the behaviour of both conditioned by particular local configur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(35 citation statements)
references
References 7 publications
0
33
0
2
Order By: Relevance
“…These activities take the form of direct action, protests and negotiations between different groups (see review in Justino et al., ). They tend to emphasize areas that are neglected in more militarized international peace‐building missions, such as the role of local‐level peace building, and the communities’ psychosocial, relational and spiritual needs (Autesserre, ; El‐Bushra, ; Hunt and Posa, ; Justino et al., ; Mazurana and McKay, ).…”
Section: Opportunities and Barriers To Women's Involvement In Peace Bmentioning
confidence: 99%
See 1 more Smart Citation
“…These activities take the form of direct action, protests and negotiations between different groups (see review in Justino et al., ). They tend to emphasize areas that are neglected in more militarized international peace‐building missions, such as the role of local‐level peace building, and the communities’ psychosocial, relational and spiritual needs (Autesserre, ; El‐Bushra, ; Hunt and Posa, ; Justino et al., ; Mazurana and McKay, ).…”
Section: Opportunities and Barriers To Women's Involvement In Peace Bmentioning
confidence: 99%
“…However, most evaluations of these initiatives have found that, even though gender roles may change during the conflict and women may play crucial roles in conflict prevention and peace building, gender identities tend to appear unchanged in the post‐conflict period (Adam, ; Date‐Bah, ; Handrahan, ; Justino, , ; Kumar, ; Rubin, ; de Watteville, ). Women are again excluded from formal peace and political processes beyond the immediate local (family or community) level (Castillejo, ; El‐Bushra, , ; Justino et al., ; Kumar, ).…”
Section: Introductionmentioning
confidence: 99%
“…As attention to the agenda grew, so scholarship concentrated on a select number of key issues and sites in which WPS was understood to happen. Of the ten most-cited pieces on WPS in our survey, it is not surprising that most focus primarily on the politics of the United Nations Security Council (Shepherd, 2008;Tryggestad, 2009;Bell and O'Rourke, 2010;Puechguirbal, 2010;Willett, 2010;Gibbings, 2011;Pratt and Richter-Devroe, 2011;Shepherd, 2011) with only two emphasizing the circulation of UNSCR 1325 beyond the UN (El-Bushra, 2007;McLeod, 2011). Significant fractions of the literature address issues of wartime sexual violence (for example, Simic, 2010; Aroussi, 2017; Reilly, 2018); women's inclusion in peacekeeping (for example, Henry, 2012;Karim, 2017;Deiana and McDonagh, 2018) or WPS as grounds for humanitarian intervention (for example, Dharmapuri, 2013;Davies et al, 2015), with contestations within the UN system fundamental in each instance.…”
Section: Map and Territorymentioning
confidence: 99%
“…First, to justify their inclusion in talks, women are portrayed as being inherently more peaceful, as more willing to be bridge builders and to seek consensus. 12 These characteristics lead to women being valued for their ability to create transformative change through their participation. 13 As Charlseworth notes, 'although an argument for women's participation could be based on equality, it is typically made on the basis of women's utility to peace.'…”
Section: Connecting Presence and Influencementioning
confidence: 99%